KOALISI DALAM SISTEM DEMOKRASI PRESIDENSIAL INDONESIA : Faktor faktor Kerapuhan Koalisi Era Presiden Yudhoyono - Haris, Syamsuddin (Pusat Penelitian Politik, 2011)
Although the concept ofcoalition is only prevalent in parliamentary democratic system but multiparty presidential system scheme which is applied in Indonesia necessitates the existence ofcoalition among its party Thepresence of Coalition is necessary to minimize the risk ofpolitical deadlock in relations between President andParliament on the one hand and due to built effectiveness in the government as the outcome ofgeneral electionBut in fact political coalition do not guarantee effectiveness in government administration even on the contraryit has become a prison for president because opposition comes from inside of The Parliament which also partof the coalition member in government In the era ofPresident Yudhoyono there are three importantfactors thatlead to fragility of the coalition the coalition design factor personalityfactor of the President and character ofthe party in theparliament In order to Built effectiveness in government which requires restructuring the coalitionform especially related to coalition base political nature of the agreement and contract among the members ofcoalition scope ofmaterial agreement and internal mechanism in the coalition in thefuture the effectiveness isalso going to be base on restructuring general election format to become national general election to elect President and Vice President and members ofparliament and local elections to choose head oflocal governmentprovince and district and members of local house of representatives)